2022
DOI: 10.3390/ijerph19031705
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Study on Scientific Articles in Health Communication: A Science Mapping Analysis in Web of Science

Abstract: The COVID-19 pandemic continues to cause a collapse in the health systems and econo-mies of many countries around the world, after 2 years of struggle and with the number of cases still growing exponentially. Health communication has become as essential and necessary for control of the pandemic as epidemiology. This bibliometric analysis identifies existing contributions, jointly studying health communication and the pandemic in scientific journals indexed. A systematic search of the Web of Science was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 77 publications
0
13
0
1
Order By: Relevance
“…Based on the process followed by De las Heras et al (2022) in their article on business management of happiness, the term "public relations" was ultimately considered to be an essential concept in the publications searched, given the focus of the study. Alongside this term, the concepts of "happiness" or "well-being" appear in the publications searched.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the process followed by De las Heras et al (2022) in their article on business management of happiness, the term "public relations" was ultimately considered to be an essential concept in the publications searched, given the focus of the study. Alongside this term, the concepts of "happiness" or "well-being" appear in the publications searched.…”
Section: Methodsmentioning
confidence: 99%
“…The main objective of this communication is to influence individual and collective decisions that lead to improved health (Renaud and de Sotelo, 2007). Therefore, health communication plays a determining role in society, and the ability to communicate quickly and transparently is essential for the effective management of a public health emergency (De las Heras-Pedrosa et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this context, a recent review by Liu et al (2022) based on a scientometric analysis of the performance of social science research on COVID-19, covering the landscape, research fields, and international collaborations, represents a notable departure from the prevalent focus of earlier studies. Representing a linguistic focus, another recent study by Heras-Pedrosa et al (2022) consisted of a systemic analysis of publications in health communication and COVID-19. It found that, in 2020, concepts related to mental health, mass communication, misinformation, and communication risk were more frequently used, and in the succeeding year (2021), vaccination, infodemic, risk perception, social distancing, and telemedicine were the most prevalent keywords.…”
Section: Previous Studiesmentioning
confidence: 99%